Consumer response due the social media marketing activities of Indonesia top brand healthy snack - Novrima, Veira Dwi; Yunus, Ulani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Purpose: A healthy lifestyle is being carried out by many people, including in Indonesia, especially during the shifting era of COVID-19. Everyone is consuming nutritious food, one of which can be done by consuming healthy snacks. The purpose of this study was to determine the impact of social media marketing activity carried out by Soyjoy, as a Top Brand Healthy Snack in Indonesia, especially on awareness and purchase intention from consumers. Research design, data, and methodology: A quantitative approach with the type of survey research through distributing questionnaires to 400 consumers as well as Soyjoy Instagram followers, sent via direct messages feature, using purposive sampling technique for 3 months. 89.5 persen or a total of 358 respondents filled out the questionnaire. Data analysis based on PLSSEM. Results: This study shows that social media marketing activities have a positive effect on brand awareness and purchase intention directly, and indirectly brand awareness can mediate the relationship between social media marketing and purchase intention. Significantly, Soyjoy's social media marketing is more capable of influencing brand awareness than purchase intention. Conclusions: This study also proposes that brands can develop social media marketing activities to increase the significance value of consumer awareness and purchase intention, especially in the pandemic era, the promotional media that can be maximized is social media.